A simplified primary aldosteronism surgical outcome score is a useful prediction model when target organ damage is unknown – Retrospective cohort study. (May 2021) - Suurd, Diederik P.D.; Visscher, Wouter P.; Vorselaars, Wessel M.C.M.; van Beek, Dirk-Jan; Spiering, Wilko; Borel Rinkes, Inne H.M.; Valk, Gerlof D.; Vriens, Menno R.; ,; Zarnegar, Rasa; Fahey, Thomas J.; Duh, Quan Y.; et al.
Abstract: Background: Cure of hypertension after adrenalectomy for primary aldosteronism is no certainty and therefore preoperative patient counseling is essential. The Primary Aldosteronism Surgical Outcome (PASO) Score is a useful prediction model with an area under the curve (AUC) of 0.839. The PASO Score includes 'Target Organ Damage' (TOD) (i.e., left ventricular hypertrophy and/or microalbuminuria), which is often unavailable during preoperative counseling and might therefore limit its use in clinical practice. We hypothesized that the PASO score would still be useful if TOD is unknown at time of counseling. Therefore, we aimed to examine the predictive performance of the simplified PASO Score, without taking TOD into account. Materials and methods: In this retrospective cohort study, patients who underwent unilateral adrenalectomy between 2010 and 2016 in 16 medical centers from North America, Europe and Australia were included. TOD was unknown in our database and therefore assigned as absent. Patients were classified as complete, partial or absent clinical success using the PASO consensus criteria. Results: A total of 380 (73.9%) patients were eligible for analysis. Complete, partial and absent clinical success were observed in 29.5%, 55.8% and 14.7% of patients, respectively. The simplified PASO Score had an AUC of 0.730 (95% confidence interval 0.674–0.785) in our total cohort. Conclusion: Without taking TOD into account, the simplified PASO Score had a lower predictive value as compared to the original derivation cohort. Ideally, the complete PASO Score should be used, but when data on TOD are not readily available, the simplified PASO Score is a useful and reasonable alternative. Highlights: We aimed to examine the predictive performance of the PASO Score, without taking 'target organ damage' (TOD) into account. This simplified PASO Score had a lower predictive value as compared to the PASO Score in the original derivation cohort. The simplified PASO Score increases the applicability of the model and is reasonable for clinicians to use in daily practice. Ideally, the complete PASO Score should be used, but the simplified PASO Score is a useful and reasonable alternative.